Rapid bedside measurement of reactive oxygen species in neonates: a pilot study - Iijima, Yuta; Endo, Mamiko; Shiohama, Tadashi; Osone, Yoshiteru; Kazumura, Kimiko; Shimojo, Naoki; Hamada, Hiromichi (Frontiers in Pediatrics, 2025)
IntroductionBiomarkers for the early detection of severe neonatal conditions, such as necrotizing enterocolitis and sepsis, remain inadequate. Reactive oxygen species (ROS) produced during neutrophil activation are emerging as potential biomarkers of these diseases. This study aimed to evaluate the feasibility of bedside ROS measurement and establish baseline levels in neonates.MethodsUsing the FLP-H4200 fluorescence-based system, OCl− were measured from 3 μl of whole blood. Twenty neonates (13 preterm and seven full-term) were included. On postpartum day 4, OCl− levels were measured using residual blood samples.ResultsBaseline OCl− levels averaged 31,340 ± 10,674 and 26,022 ± 11,363 in full-term and preterm neonates, respectively (p = 0.35). No significant correlations were observed between OCl− levels and gestational age, birth weight, maternal milk intake, bilirubin, and C-reactive protein levels.DiscussionThe FLP-H4200 system is feasible for rapid and minimally invasive ROS measurement in neonates. Although no significant associations with clinical factors were identified, elevated ROS levels compared with those in adults suggest neonatal adaptation to oxidative stress. Further research is required to evaluate ROS dynamics progressively and their clinical use in neonatal disease prediction.